The role of SIRT3 in homeostasis and cellular health - Trinh, Dennison; Al Halabi, Lina; Brar, Harsimar; Kametani, Marie; Nash, Joanne E. (Frontiers in Cellular Neuroscience, 2024)
Mitochondria are responsible for maintaining cellular energy levels, and play a major role in regulating homeostasis, which ensures physiological function from the molecular to whole animal.Sirtuin 3 (SIRT3) is the major protein deacetylase of mitochondria. SIRT3 serves as a nutrient sensor; under conditions of mild metabolic stress, SIRT3 activity is increased. Within the mitochondria, SIRT3 regulates every complex of the electron transport chain, the Kreb's and Uric acid cycles, as well as the mitochondria membrane potential, and other free radical scavengers. This article reviews the role of SIRT3 in regulating homeostasis, and thus physiological function.We discuss the role of SIRT3 in regulating reactive oxygen species (ROS), ATP, immunological function and mitochondria dynamics.